2020
DOI: 10.1177/2042098620968310
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing cascades in persons with Alzheimer’s disease: engaging patients, caregivers, and providers in a qualitative evaluation of print educational materials

Abstract: Introduction: Prescribing cascades occur when the side effect of a drug is misinterpreted as a new medical condition, and a second drug is prescribed to address the side effect. Persons with Alzheimer’s disease (AD) are at increased risk of prescribing cascades due to greater multimorbidity, polypharmacy, and complexity of care. The objective of this study was to evaluate educational materials about prescribing cascades in persons with AD, and elicit input on their use in a future trial. Methods: We interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Morris et al, in 2022 using the prescription sequence symmetry analysis (PSSA) methodology, identified 281 unique index drug—marker drug class dyads published as prescribing cascade signals 37 . While it is important to recognize the prescribing cascade signals identified by PSSA do not establish causality, some of the signals identified have been validated in formalized studies 44‐49 . In this study, we found that half of the index and marker drugs associated with the prescribing cascades signals involve a potentially inappropriate medication.…”
Section: Discussionmentioning
confidence: 75%
“…Morris et al, in 2022 using the prescription sequence symmetry analysis (PSSA) methodology, identified 281 unique index drug—marker drug class dyads published as prescribing cascade signals 37 . While it is important to recognize the prescribing cascade signals identified by PSSA do not establish causality, some of the signals identified have been validated in formalized studies 44‐49 . In this study, we found that half of the index and marker drugs associated with the prescribing cascades signals involve a potentially inappropriate medication.…”
Section: Discussionmentioning
confidence: 75%
“…Further, despite widespread efforts to recruit for our self-referral stream, only two people self-referred for interviews. In our recruitment materials, we did not use the phrase ‘prescribing cascade’ specifically, which is a different approach than that used by Bloomstone and colleagues [ 33 ]. In their study, which developed and tested education materials for people living with dementia and their caregivers about prescribing cascades, investigators used an increasingly recognized cascade, calcium channel blocker → edema → diuretic, to introduce the concept.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from interviews with community-dwelling patients with ADRD, their caregivers, and providers offer further support for the feasibility of activating caregivers to participate in the deprescribing process using educational mailings. Bloomstone et al 29 found strong support for providing materials to encourage the caregivers to initiate a conversation with the provider about educational materials on prescribing cascades among patients with ADRD and caregivers but also identified a need to understand how the materials might motivate such a conversation. The study advances these findings in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…Research also supports the importance of the patient/caregiver–provider communication to achieve clinical outcomes through engagement and shared decision-making. 29 , 31 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation